A population-based estimation of breast cancer recurrence in northeast Italy with administrative healthcare databases - Fabiola Giudici; Federica Toffolutti; Stefano Guzzinati; Francesco Schettini; Marina Bortul; Silvia Francisci; Manuel Zorzi; Sara De Vidi; Daniela Pierannunzio; Luigino Dal Maso (Breast)
Background/Aim: Information on the long-term frequency of recurrence is of paramount importance for the increasing number of women living several years after breast cancer (BC) diagnosis and for their caregivers.The study aims to estimate the cumulative incidence of recurrence until 10 years after diagnosis in Italian women diagnosed with BC using population-based cancer registries. Methods: Women diagnosed with stage I to III BC during 2004–2010 from Friuli Venezia Giulia and Veneto (Italy) cancer registries were included (n = 5825). Recurrence status after a disease-free period was ascertained through individual-level linked databases using treatment or procedure codes from claims. Cumulative incidence of recurrence was calculated in the presence of competing risks (second cancer or death). Results: During a median follow-up of 13.5 years, 1522 out of 5825 women experienced a recurrence with an estimated 10-years cumulative incidence of 20.8 % (95 %CI:19.7–21.8 %), decreasing from 23.7 % in 2004–2006 to 18.5 % in 2007–2010. Women younger than 40 years (40.5 %), with stage III (41.8 %) and triple-negative BC (32.5 %) showed a higher 10-year incidence of recurrence.At 10 years after a BC diagnosis, 83.9 % of women were alive: 67.5 % without any cancer-related events, 12.4 % after recurrence and 4.0 % after second primary cancer. 10-years survival was higher than 90 % for women with stage I BC and 58.1 % for those with stage III (3.2 % and 27.3 % deaths after recurrence, respectively). Discussion: This Italian study provide detailed population-based information on the incidence of recurrence and other outcomes after BC and may be replicated in other Italian and European areas.